Vermilion drift [compact disc, unabridged] : a novel - Krueger, William Kent (Krueger, William Kent. Cork O'Connor mystery., 2010)
When the Atomic Energy Commission puts the Vermilion One Mine on its shortlist of potential sites for storage of nuclear waste, a barrage of protest erupts in Tamarack County, Minnesota, and Cork O'Connor is hired to head security. His first day on the job, Cork stumbles across a secret room with the remains of six murder victims inside. Five appear to be nearly half a century old - connected to what the media had dubbed 'The Vanishings,' a series of unsolved disappearances in the summer of 1964, when Cork's father was sheriff in Tamarack County. But the sixth has been dead less than a week. What's worse, two of the bodies - including the most recent victim - were killed using Cork's own gun, one handed down to him from his father. As Cork searches for answers, he must dig into the darker passages of his family's past. New threats surface, and unless Cork can unravel the tangled thread of clues quickly, more death is sure to come to Tamarack County.